NKT Cell Levels in Patients with Type-I Hypersensitivity - Ilhan, Fulya; Godekmerdan, Ahmet; Akbulut, Handan; Bulut, Vedat (Turkish Soc Immunology, 2005)
Natural killer T cells (NKT) express both NK receptors CD56, CD161, the latter being a member of the killer activator receptor (KAR) family and all express TCR alpha chain. These cells can rapidly produce interleukin 4 (IL-4) and interferon gamma (IFN-gamma). NKT cells have a regulatory role on the immune system. In this study we compared NK and NKT cells levels between patient and control group. The patient group included those with type I hypersensitivity (19 rhinitis and 17 asthma patient, total 36). Our results showed that both rhinitis and asthma patients displayed NKT cells levels higher than controls. But with NK cells no difference were found between patient and control groups. These results indicate that these cells may play an important role in the development of asthma and rhinitis.
Keywords: NKT cells; asthma; allergic rhinitis